SUKSESI VEGETASI PADA LAHAN BEKAS PENAMBANGAN EMAS RAKYAT DI KECAMATAN MONTERADO KABUPATEN BENGKAYANG - Isnaniarti, U Nur; Ekyastuti, Wiwik; Ekamawanti, Hanna Artuti (JURNAL HUTAN LESTARI, 2018)
This study aims to obtain information about the succession levels of natural vegetation on ex – community gold mining in Monterado. The method of this research was survey method through vegetation analysis by double plot size 20 m x 20 m. Placement of plots dileberately based on the tailing period of ex – community gold mining which were : < 1 year, 2-3 years, 5-7 years, and > 10 years. The result showed that kinds of shrub found in all age level of ex – community gold mining area. The type of woody plants at the seedling found in all period of ex – community gold mining area, whereas sapling, pole and tree only found in ex – community gold mining at age level > 10 years. Based on the vegetation analysis, it showed that Ischaemum rugosum and Melastoma malabathricum L. dominanted at all age level of ex – community gold mining. Seedling in the ex – community gold mining at all age level were dominanted by Dillenia suffruticus. The index of species diversity showed that it was still low on ex – community gold mining in Monterado.Until the age of tailing > 10 years, succession was still in the level of competition, so it was concluded to be slow. To accelerate succession, revegetation, land restoration, and people awareness should be undertaken.Keyword : Gold mining, Monterado Sub District, Succession of Vegetation.